"And Binding with Briars, my Joys and Desires": Discussion of Janine de Peyer's "Unspoken Rhapsody". Issue 1 (2nd January 2022) - Burton, Noelle
Abstract : This paper discusses Janine de Peyer's "Unspoken Rhapsody: Female Erotic Countertransference and the Dissociation of Desire, " elaborating on the professional and clinical aspects of working with female erotic countertransference with male patients, with a focus on dissociation and containment in these contexts. Perspectives from evolutionary psychology and affective neuroscience are offered to better understand how female analyst/male patient dyads differ from that of male analyst/female patient.